PERSEPSI MAHASISWA AKUNTANSI MENGENAI KEADILAN, SISTEM PERPAJAKAN, DISKRIMINASI, DETEKSI DAN KUALITAS PELAYANAN TERHADAP ETIKA ATAS PENGGELAPAN PAJAK (TAX EVASION) - Ryandika, Agnes Deby; Achyani, Fatchan (Journal of Economic, Bussines and Accounting (COSTING), 2025)
This study aims to analyze the influence of fairness, tax system, discrimination, detection, and service quality on tax evasion based on accounting students' perceptions. A quantitative approach with a positivism paradigm was used, employing primary data collected through a Google Form questionnaire. The sample consisted of 96 undergraduate accounting students from Universitas Muhammadiyah Surakarta, class of 2021, who had completed taxation courses. The sampling technique was purposive, using the Slovin formula from a population of 2,318 students. Variables were measured using a 5-point Likert scale and analyzed using multiple linear regression with SPSS. The findings indicate that fairness and detection significantly influence tax evasion, while the tax system, discrimination, and service quality do not have a significant impact. This research contributes to understanding the factors influencing perceptions of tax evasion among accounting students and provides recommendations for future studies to expand sample coverage and explore additional variables.